Hidden GBV: Women and substance use - Moir, Eilidh; Gwyther, Sophie; Wilkins, Heather; Boland, Gillian (Frontiers in Psychiatry, 2022)
Gender based violence (GBV) is disproportionately higher in women who use substances. This vulnerable population are also at a disadvantage when it comes to accessing harm reduction services. Between May and October 2021 there were 77 cases discussed at Multi-Agency Risk Assessment Conferences (MARAC) in Dundee. The majority of these cases (62) had substance misuse as a risk factor. It is at these meetings that the vulnerability of women comes to the fore and issues of violence are highlighted. During this time period, 44 cases involved the victim being strangled/choked or suffocated and 43 cases had weapons as a risk factor. 56 of the cases included children. The issue of GBV or Intimate Partner Violence (IPV) is often hidden, especially in and by those affected by substance use. Women experiencing GBV and IPV require specialist support, often across different services to address different needs. How well violence against women is understood in relationships that are affected by drugs is difficult to determine. In many instances it isn’t until a MARAC meeting, or similar crisis point is met, that the extent of the abuse is highlighted. What services can provide singularly is limited in many of these cases but joint-working and innovative practices, such as the Gendered Services Project in Dundee strive to change the landscape of service delivery.